Export behaviour and attitudes of Australasia meat industry firms : a North American market focus : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in Agricultural Economics at Massey University - Waggoner, Daniel B (Massey University, 1993)
The merchandising of agricultural commodities and products has assumed an increased international dimension over the past two decades. Meat export firms in both Australia and New Zealand continue to play an important role as a major provider of export earnings, technological innovation, and employment. During the last several years, a body of literature has attempted to provide a more satisfactory explanation of differences in the export performance of the firm. Although previous studies contribute to a greater insight into export behaviour and attitudes, they are confounded by methodological and conceptual limitations which diminish the insights they offer for those involved in the meat export industry. Studies of export marketing phenomena in different social, cultural, economic, political and institutional settings can provide improved understanding of the export behaviour and attitudes of firms in different environments. This study is undertaken to investigate the export behaviour and attitudes of Australasia meat export firms, particularly toward the North American marketplace. The study is unique in two respects. First, it compares the overseas practices of Australia and New Zealand firms rather than the characteristics of their home operations. Second, the study attempts to hold constant differences in objectives and/or strategies which are due to the idiosyncrasies of particular markets or industries. It does this by limiting analysis to one overseas market -- North America. This research effort includes most types of previously examined firm-related variables but gives particular attention to manager-related variables, especially managers' perceptions of exporting. The Geobusiness Model is presented as a framework to facilitate the operationalisation of the variables and measure the constructs utilised in the study. Research questions surrounding the relationship between business strategy, structure, and performance in the North American marketplace are developed and investigated. Primary data for the study is gathered from a random sample survey of 89 meat export firms based in Australasia (i.e., Australia and New Zealand), utilising a self-administered postal questionnaire targeted towards pre-identified senior managers. The sample frame is derived from a register (list) provided by the United States Department of Agriculture. The empirical survey data obtained arc analysed by country and compared to each other using frequency distribution analyses, matrix analyses and Spearman rank-order correlation (rho). Significant differences among countries are identified by using the Student's t-Test. Though the study is exploratory in nature, the results of this interdisciplinary investigation suggest some common themes consistent with previous research. It was found that even among firms within the same industry, their attitudes and response to various variables differ. This demonstrates the importance of using both export involvement and export attitude dimensions when attempting to segment firms. In sum, the findings and conclusions from the study should be of practical use to business enterprises, government trade policy officials and industry associations in identifying the areas of support and marketing strategy in greatest need of review and improvement. While these results cannot be freely generalised beyond the initial population, they provide some understanding of the theoretical and empirical issues related to the export marketing performance and behaviour of the firm. Future research efforts will find merit in examining further the relationship between the various variables presented and the unidimensional and multidimensional measure of export performance and attitudes among firms.
Keywords: Export marketing; Meat exports; Meat export, Australia; Meat export, New Zealand